Propofol in Neurotrauma - Murthy, TVSP (Indian Journal of Neurotrauma, 2008)
Propofol (2,6-diisopropylphenol) is one of the most popular agents used for induction of anesthesia and long-term sedation, owing to its favorable pharmacokinetic profile, which ensures a rapid recovery even after prolonged administration. Propofol is used widely as a sedative agent in neurosurgical critical care because it is generally assumed that it has properties that are advantageous to the injured brain. Propofol is believed to maintain, or even improve, cerebral autoregulation, indeed even high doses of this drug do not obtund autoregulation or carbon dioxide reactivity. A neuroprotective effect, beyond that related to the decrease in cerebral metabolic rate for oxygen, has been shown to play an important role in the so-called multimodal neuroprotection, a global strategy for the treatment of acute injury of the brain that includes preservation of cerebral perfusion, temperature control, prevention of infections, and tight glycaemic control.
Keywords: propofol; neuroprotection; traumatic brain injury